Politische Steuerung und Zielperspektiven einer sozial-integrativen Stadtentwicklung im Bundesland Brandenburg - Rolfes, Manfred; Wilhelm, Jan Lorenz (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
Urban policies — no matter whether on a communal, regional or national level — are characterized by forward-looking, forward-planning procedures. Self-critical reflections on the effects or the efficiency of already implemented policies are in general speaking not very common. Two reasons are often mentioned. On the one hand profound methodical problems can make evaluations of urban policies very complicated. On the other hand if there do exist evaluation-reports they are often left out of consideration for the ongoing planning of new urban policies for lack of time. Based on empirical studies and evaluations in the state of Brandenburg this article wants to discuss consequences for the control and management of integrated urban developing policies.